Common Techniques, Success Attack Factors and Obstacles to Social Engineering: A Systematic Literature Review - António Lopes; Henrique S. Mamede; Leonilde Reis; Arnaldo Santos (Ital Publication, 2024)
Knowledge of Social Engineering is crucial to prevent potential attacks related to organizational Information Security. The objective of this paper aims to identify the most common social engineering techniques, success attack factors, and obstacles, as well as the good practices and frameworks that could be adopted concerning their mitigation. As an analysis methodology, a Systematic Literature Review was carried out. The findings revealed that the discussion about SE attacks has increased and that the most imminent threat is phishing. Exploiting human vulnerabilities is a growing threat when the attack is not carried out directly through technical means. There continue to be more technical attacks than non-technical attacks. Encouraging organizational security prevention, like training, education, technical controls, process development, defense in detail, and the development of security policies, should be considered mitigating factors for the negative impact of SE attacks. Most SE frameworks/models are focused on attack techniques and methods, mostly on technical components, decorating human factor. As a novelty, we found the opportunity to develop a new framework that could improve coverage of the gaps found, supported on security international standards, that could help and support researchers in developing their work, understanding open research topics, and providing a clearer understanding of this type of threat. Doi: 10.28991/ESJ-2024-08-02-025 Full Text: PDF